2007
DOI: 10.1111/j.1463-5224.2007.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rebound tonometer (TonoVet®) with the applanation tonometer (TonoPen XL®) in normal Eurasian Eagle owls (Bubo bubo)

Abstract: The results suggest that readings from the rebound tonometer significantly overestimated those from the applanation tonometer and that the rebound tonometer was tolerated well because of the rapid and minimal stress-inducing method of tonometry in the Eurasian Eagle owls, even without topical anesthesia. Further studies comparing TonoVet with manometric measurements may be necessary to employ rebound tonometer for routine clinical use in Eurasian Eagle owls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
91
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 16 publications
(15 reference statements)
8
91
1
7
Order By: Relevance
“…Rebound tonometer was designed for use in animals with small eyes and has recently been used in birds, such as bald eagle (21.5±1.7mm Hg) (Kuhn et al 2013), Megascops asio (11±1.9mm Hg) (Harris et al 2008), Spheniscus dermersus (31.77±3.3mm Hg) (Gonzalez-Alonso-Alegre et al 2015), Bubo bubo (10:45±1.64mm Hg) (Jeong et al 2007) and Phoenicopterus ruber ruber (9.5±1.7mm Hg) (Meekins et al 2015a). Rebound tonometer reference values overestimate IOP compared to applanation tonometry in Eurasian eagle owls (Jeong et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rebound tonometer was designed for use in animals with small eyes and has recently been used in birds, such as bald eagle (21.5±1.7mm Hg) (Kuhn et al 2013), Megascops asio (11±1.9mm Hg) (Harris et al 2008), Spheniscus dermersus (31.77±3.3mm Hg) (Gonzalez-Alonso-Alegre et al 2015), Bubo bubo (10:45±1.64mm Hg) (Jeong et al 2007) and Phoenicopterus ruber ruber (9.5±1.7mm Hg) (Meekins et al 2015a). Rebound tonometer reference values overestimate IOP compared to applanation tonometry in Eurasian eagle owls (Jeong et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Rebound tonometer reference values overestimate IOP compared to applanation tonometry in Eurasian eagle owls (Jeong et al 2007). Testing the accuracy and reproducibility of IOP measurements obtained with the TonoVet rebound tonometer, Reuter et al (2010) reported that in chickens, results with this device correlated less with manometric values than in dogs, cats and horses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing rebound tonometry and a manometer showed that, in some birds, IOP was overestimated, while it was underestimated in others. However, even with these variations, the values obtained are considered useful for clinical application (Jeong et al 2007, Reuter et al 2010, Wojick et al 2013. To minimize such oscillations, it is suggested that a single method be used for a particular species (Meekins et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported intervals of 1, 2, and 10 minutes (LEIVA et al, 2006;JEONG et al, 2007;LÓPEZ-CABALLERO et al, 2007;PEREIRA et al, 2011). Although these experiments were not using a "stress model", simply Table 1 -Values of mean intraocular pressure (IOP) in mmHg of horses of different ages, measured with the rebound tonometer with and without twitch.…”
Section: Discussionmentioning
confidence: 99%